"There Is No Face Like Home": Ratings for Cultural Familiarity to Own and Other Facial Dialects of Emotion With and Without Conscious Awareness in a British Sample. (October 2019) - Tsikandilakis, Myron; Kausel, Leonie; Boncompte, Gonzalo; Yu, Zhaoliang; Oxner, Matt; Lanfranco, Renzo; Bali, Persefoni; Urale, Poutasi; Peirce, Jonathan; López, Vladimir; Tong, Eddie Mun Wai; William, Hayward; et al.
The dialects theory of cross-cultural communication suggests that due to culture-specific characteristics in the expression of emotion, we can recognise own-culture emotional expressions more accurately than other-culture emotional expressions. This effect is suggested to occur due to the nonconvergent social evolution that takes place in different geographical regions. Based on the evolutionary value of own-culture social signals, previous research has suggested that own-culture emotional expressions can be appraised without conscious awareness. The current study tested this hypothesis. We developed, validated, and made open access what is to our knowledge the first labelled, multicultural facial stimuli set, including freely expressed and Facial Action Coding System instructed emotional expressions. We assessed emotional recognition and cultural familiarity responses during brief backward-masked presentations in British participants. We found that emotional recognition and cultural familiarity were higher for own-culture faces. A Bayesian analysis of face-detection and emotional-recognition performance revealed that faces were not processed subliminally. Further analysis of awareness, using hits (correct detection/recognition) and misses (incorrect detection/recognition), showed that face-detection hits were a necessary condition for reporting higher familiarity for own-culture faces. These findings suggest that the own-culture emotional recognition advantage is preserved under conditions of backwards masking and that the appraisal of cultural familiarity involves conscious awareness.